Estudio de los corales cyathópsidos (Rugosa) del Viseense superior de la Unidad de la Sierra del Cas - Rodríguez, Sergio; Hernando, José Miguel; Rodríguez-curt, Lucía (Coloquios de Paleontología, 2004)
Dissepimented rugose corals are frequent in the Sierra del Castillo Unit (Guadiato Area, Ossa Morena) which is composed mainly of Viséan limestones. Cyathopsid corals from Sierra del Castillo, Sierra de la Estrella (both near Espiel, Córdoba) and Antolín (near Peñarroya, Córdoba) have been studied. Seven species belonging to the genera Siphonophyllia, Caninia, Pseudozaphrentoides, Haplolasma and Caninophyllum have been described.